Controversies in the management of stage III non-small-cell lung cancer. Issue 3 (March 2014) - Biswas, Tithi; Sharma, Neelesh; Machtay, Mitchell
Abstract : Lung cancer remains the leading cause of death in the USA and is the most common cancer both in incidence and in mortality globally (1.35 million deaths annually). Non-small-cell lung cancer accounts for >80% of all lung cancers[1] . About 35–45% of non-small-cell lung cancer patients present with locally advanced non-metastatic stage III disease. However, confirmed stage III disease represents a very heterogeneous group ranging from borderline surgical candidate with minimal mediastinal involvement to bulky mediastinal nodes or contralateral nodal involvement with significant controversy regarding optimal management in these various situations. This article specifically addresses the role of surgery, radiotherapy and chemotherapy in multimodal approach to treat stage III patients with N2/N3 involvement and controversies surrounding these recommendations.